Functional characterization of MANNOSE-BINDING LECTIN 1, a G-type lectin gene family member, in response to fungal pathogens of strawberry. (11th October 2022) - Ma, Lijing; Haile, Zeraye Mehari; Sabbadini, Silvia; Mezzetti, Bruno; Negrini, Francesca; Baraldi, Elena
Abstract: The mannose-binding lectin gene MANNOSE-BINDING LECTIN 1 ( MBL1 ) is a member of the G-type lectin family and is involved in defense in strawberry ( Fragaria × ananassa ). Genome-wide identification of the G-type lectin family was carried out in woodland strawberry, F. vesca, and 133 G-lectin genes were found. Their expression profiles were retrieved from available databases and indicated that many are actively expressed during plant development or interaction with pathogens. We selected MBL1 for further investigation and generated stable transgenic FaMBL1 -overexpressing plants of F. × ananassa to examine the role of this gene in defense. Plants were selected and evaluated for their contents of disease-related phytohormones and their reaction to biotic stresses, and this revealed that jasmonic acid decreased in the overexpressing lines compared with the wild-type (WT). Petioles of the overexpressing lines inoculated with Colletotrichum fioriniae had lower disease incidence than the WT, and leaves of these lines challenged by Botrytis cinerea showed significantly smaller lesion diameters than the WT and higher expression of CLASS II CHITINASE 2-1 . Our results indicate that FaMBL1 plays important roles in strawberry response to fungal diseases caused by C. fioriniae and B. cinerea . Abstract : FaMBL1 plays a role in strawberry defense against fungal pathogens, and transgenic octoploid strawberries overexpressing FaMBL1 are less susceptible to anthracnose and grey mould.